Primary cutaneous marginal zone lymphoma (immunocytoma like) with lymphoepithelioid or Lennert′s lymphoma like involvement of nodes - Tanuja Shet; Rajan Basak; Sridhar Epari (Indian Journal of Pathology and Microbiology, 2012)
Primary cutaneous marginal zone lymphomas (PCMZL) have a wide range of morphology from tumors with monocytoid B cells to those composed entirely of plasma cells and the T-cell rich variants. We report a 60-year-old male with a PCMZL rich in plasma cells of the foot with a lymphoepithelioid-like pattern of dissemination to the lymph nodes posing problems in the diagnosis. The patient had a lesion on the dorsum of the foot which histologically revealed dense perivascular collections of lymphoid cells and plasma cells amidst fibrous tissue. Though the plasma cells did show light chain restriction, CD20 and CD3 did not reveal an overwhelming B/T-cell population and hence a diagnosis of a reactive process was offered. Subsequently the patient developed inguinal nodes with diffuse loss of architecture and replacement by epithelioid histiocytes and reactive T cells with few large B cells (lymphoepithelioid-like pattern). On pathology review it was realized that the two lesions may be related and clonality studies were asked for. The skin lesion showed clonally rearranged IgH receptor while the T-cell receptor rearrangement was negative. The patient developed disseminated disease and received six cycles of chemotherapy with partial response and 6 years after the initial presentation was alive with nonprogressive disease. Thus, the polymorphous background in PCMZL is evolving and an immunocytoma-like tumor can show a T-cell rich or Lennert′s like growth pattern of spread and early recognition these odd patterns may aid in appropriate management of patients.